Process Optimization and Application of Lipase Immobilized on Phenol Amino Modified MCM-41 - Qian LI; Xiangbing ZENG; Xitong SUN; Xiaoyi CHEN; Miao LI; Tianyu WANG; Fan HUANG; Fanghong SUN; Xianzhen LI (Shipin gongye ke-ji, 2025)
In order to construct a new catalytic system of immobilized lipase and improve the stability of enzyme, the phenol amino modified ordered mesoporous material (MCM-41) was introduced for the study of lipase immobilization. The immobilized enzyme was also applied to the actual reaction system. The optimized conditions of lipase immobilization were as follows: Immobilization temperature of 30 ℃, immobilization pH of 8.0, immobilization time of 7 h, initial enzyme concentration of 4 mg/mL, and the enzyme loading was 26.40 mg/g. Meanwhile, the optimum reaction temperature of the immobilized enzyme was 50 ℃, and the optimum reaction pH was 7.0, together with the highest enzyme activity was 4108±34.74 U/g carrier. The immobilized enzyme was recycled for eight times, and it retained 54.70% of the initial enzyme activity. While after 30 days of storage at 4 ℃, it still kept 71.10% of the initial enzyme activity. In addition, the immobilized enzyme was used to catalyze the synthesis of hexyl laurate, and the highest conversion of lauric acid was 65.38%. It was indicated that the lipase immobilized on phenol amino modified MCM-41 exhibited high enzyme activity and good stability. When it was applied in the actual catalytic reaction, the immobilized enzyme displayed high catalytic efficiency. Furthermore, it was proved that phenol amino modification was a green and effective modification strategy, which could provide ideas for further application of phenol amino coating.